Modern production of laboratory animals - Toft, Martin (Henry Stewart Talks, 2015)
Ensuring microbial quality (Complex processes and Bioexclusion), Ensuring genetic quality (Breeding management and molecular testing solutions), Molecular methods and embryology applied to generate & breed complex models